2019
DOI: 10.1159/000501530
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Combined External Ventricular Drainage with Intraventricular Fibrinolysis for the Treatment of Intraventricular Haemorrhage with Acute Obstructive Hydrocephalus

Abstract: Background: Intraventricular haemorrhage (IVH) patients with acute obstructive hydrocephalus (AOH) who require external ventricular drainage (EVD) are at high risk for poor outcomes. Intraventricular fibrinolysis (IVF) with low-dose recombinant tissue plasminogen activator (rtPA) can be used to improve patient outcomes. Here, we evaluated the impact of IVF on the risk of death and the functional outcomes in IVH patients with AOH. Methods: This prospective cohort study included IVH patients with hypertensive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
(29 reference statements)
0
14
0
1
Order By: Relevance
“…If an intracerebral hemorrhage breaks into the ventricle, it may quickly lead to a rapid increase in intracranial pressure, acute dilation of the ventricle, and compression of the ventricle system by a hematoma, resulting in acute obstructive hydrocephalus [ 4 , 5 ]. These patients will develop critical disease quickly, with rapid onset, rapid progression, high mortality, and poor prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…If an intracerebral hemorrhage breaks into the ventricle, it may quickly lead to a rapid increase in intracranial pressure, acute dilation of the ventricle, and compression of the ventricle system by a hematoma, resulting in acute obstructive hydrocephalus [ 4 , 5 ]. These patients will develop critical disease quickly, with rapid onset, rapid progression, high mortality, and poor prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome of the study was poor neurological function (poor outcome) at 90 days of ictus, which was defined as mRS scores of 4 (moderately severe disability) to 6 (death) [35,37]. We also examined the following secondary outcomes: poor outcome at 30 days of ictus, mortality rate at 30 and 90 days of ictus, and incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…• Hospital course and outcomes, including length of hospitalization, discharge status (e.g., hospital discharge, transfer to another hospital, "discharged to die" decision in which almost all patients were in grave condition or dying and classified with a modified Rankin Scale (mRS) score of 5 (severe disability) at the time of discharge [35], and death in hospital); functional outcomes at 30 and 90 days of ictus, such as mRS scores ranging from 0 (no disability) to 6 (death) [36]; and death at 30 and 90 days of ictus.…”
Section: Variablesmentioning
confidence: 99%
“…23 In human medicine, CSF drainage ("CSF-TT") is used to predict the efficacy of surgical treatment in both congenital and acquired hydrocephalus patients. [9][10][11][12][13][14][15][16][17] If the clinical signs improved after lumbar CSF-TT in iNPH patients, or after external ventricular drainage in congenital or acquired hydrocephalus patients, the CSF-TT was judged Positive. In those positive patients, surgical treatments reducing CSF volume would be expected to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…8 In human medicine, the CSF-tap test (CSF-TT) (ie, drainage) is used to predict the efficacy of surgical treatment in both congenital and acquired hydrocephalus. [9][10][11][12][13][14][15][16][17] However, a recent systematic review on reliability of CSF-TT in idiopathic normal pressure hydrocephalus (iNPH) demonstrated that a negative response to CSF-TT does not necessarily imply ineligibility for shunting. 18 Recently, CSF dynamics Abbreviations: CCJ, craniocervical junction; CSF, cerebrospinal fluid; CSF-TT, CSF-tap test;…”
Section: Introductionmentioning
confidence: 99%